DAMPAK MEDIA SOSIAL TERHADAP ETIKA AKADEMIK DI KALANGAN MAHASISWA - Litriwani, Adina; Nabila; Rindiyani, T. Rahmah; Dalimunthe, Ardiansyah; Nasution, Ataina Zulfa (CV. Arsy Persada Quality, 2025)
Social media is a way of communicating between one party and another, which is done online so that people can interact with each other without being limited by space and time. The use of social media networks can have positive and negative impacts on its users. Social media has become an integral part of student life, which can offer convenience in communicating and accessing information. However, this convenience also raises challenges to academic ethics values ​​such as integrity, honesty, and responsibility. Through surveys and quantitative data analysis, this study investigates the correlation between the intensity of social media use and unethical behavior such as plagiarism, cheating on exams, and the dissemination of inaccurate information related to academic assignments. The results of the study are expected to provide a deeper understanding of the influence of social media on the formation of students' academic character and its implications for the quality of higher education. However, on the other hand, social media also has the potential to facilitate collaboration and access to diverse learning resources. These findings are also expected to be the basis for developing effective strategies and policies to promote academic ethics in the digital era.